Gypsum and Legume Residue as a Strategy to Improve Soil Conditions in Sustainability of Agrosystems of the Humid Tropics - Moura, Emanoel Gomes de; Portela, Stefanny Barros; Alencar Macedo, Vinicius Ribamar; Lima Sena, Virley Gardeny [UNESP]; Martin Sousa, Carlos Cesar; Ferreira Aguiar, Alana das Chagas (Mdpi, 2018)
Gypsum combined with leguminous residue may extend rootability and improve growth and maize grain yield. The aim of this study was to evaluate the combined effects of gypsum and leguminous residue on soil rootability in the root zone and on maize grain yield in a cohesive tropical soil. We used seven treatments: (i) control; (ii) urea; (iii) leguminous; (iv) 6 t/ha of gypsum with leguminous or (v) with urea or (vi) with both; and (vii) 12 t/ha of gypsum with urea and leguminous. Gypsum was applied in January 2010 and soil samples were analyzed in 2012-2015. Maize was sown in 2011-2013 and 2015, when maize yield was determined. Soil penetration strength and the analysis of plant tissue was performed in 2015. The leaf area index, nitrogen accumulation amount, total N concentration and amount of N remobilization were also determined in 2015. Gypsum with leguminous residue modified the root zone by increasing calcium and organic matter levels and by reducing soil penetration strength. The leaf area index and the remobilization of nitrogen to grains increased, due to greater uptake before and after tasseling. The gypsum and leguminous residue combination is a more suitable strategy to improve agrosystems in cohesive soils of the humid tropics.
Keywords: calcium; penetration strength; nitrogen remobilization